Hepatoprotective and Antioxidant Effect of Bauhinia hookeri Extract against Carbon Tetrachloride-Induced Hepatotoxicity in Mice and Characterization of Its Bioactive Compounds by HPLC-PDA-ESI-MS/MS. (14th May 2014) - Al-Sayed, Eman; Martiskainen, Olli; Seif el-Din, Sayed H.; Sabra, Abdel-Nasser A.; Hammam, Olfat A.; El-Lakkany, Naglaa M.; Abdel-Daim, Mohamed M.
Abstract : The hepatoprotective and antioxidant activity of Bauhinia hookeri ethanol extract (BHE) against CCl4 -induced liver injury was investigated in mice. BHE was administered (500 and 1000 mg/kg/day) along with CCl4 for 6 weeks. The hepatic marker enzymes: alanine aminotransferase (ALT), aspartate aminotransferase (AST), and alkaline phosphatase (ALP) were determined in the serum. The antioxidant parameters: glutathione (GSH), superoxide dismutase (SOD), glutathione peroxidase (GPx), glutathione reductase (GR), glutathione transferase (GST), and malondialdehyde (MDA) were estimated in the liver homogenate. BHE treatment significantly inhibited the CCl4 -induced increase in ALT (44 and 64%), AST (36 and 46%), ALP (28 and 42%), and MDA (39 and 51%) levels at the tested doses, respectively. Moreover, BHE treatment markedly increased the activity of antioxidant parameters GSH, GPx, GR, GST, and SOD. Histological observations confirmed the strong hepatoprotective activity. These results suggest that a dietary supplement of BHE could exert a beneficial effect against oxidative stress and various liver diseases by enhancing the antioxidant defense status, reducing lipid peroxidation, and protecting against the pathological changes of the liver. The hepatoprotective activity of BHE is mediated, at least in part, by the antioxidant effect of its constituents. The active constituents of BHE were identified by HPLC-PDA-ESI/MS/MS.